1976
DOI: 10.1300/j082v02n01_01
|View full text |Cite
|
Sign up to set email alerts
|

A Factor-Analytic Conceptualization of Attitudes Toward Male and Female Homosexuals

Abstract: A wide spectrum of opinions and beliefs concerning homosexuals was sampled, compiled into a questionnaire format, and administered to a large group of heterosexual subjects. Factor analysis yielded six independent sets of attitudes that describe the variance in heterosexual reactions to homosexuals. The relationship of sex differences and familiarity with homosexuals to variations in response style is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…Attitude researchers predicted affective responses within the parlance of ego defense. Anti-homosexual prejudice was thought to derive from personal anxiety (Millham, San Miguel, & Kellogg, 1976), sex guilt (Dunbar, Brown, & Amoroso, 1973), and fear and denial of personal homosexual tendencies (Mosher & O'Grady, 1979).…”
Section: Measuring Anti-homosexual Prejudice I: Gay Liberation and Unmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude researchers predicted affective responses within the parlance of ego defense. Anti-homosexual prejudice was thought to derive from personal anxiety (Millham, San Miguel, & Kellogg, 1976), sex guilt (Dunbar, Brown, & Amoroso, 1973), and fear and denial of personal homosexual tendencies (Mosher & O'Grady, 1979).…”
Section: Measuring Anti-homosexual Prejudice I: Gay Liberation and Unmentioning
confidence: 99%
“…Herek (1984) questioned the necessity of multifactorial scales, and ultimately concluded that only a single factor was required to conceptualize heterosexism. Herek (1984) reported four studies which drew on both earlier attitude measures (Levitt & Klassen, 1974;MacDonald et al, 1973;Millham et al, 1976;Smith, 1971) and some original items. Notably, Herek excluded items from Mosher and O'Grady (1979) arguing that the "locker room" language of these behavioral items would offend participants instead of tapping into feelings of personal threat.…”
Section: Measuring Anti-homosexual Prejudice Ii: Social Reform and MImentioning
confidence: 99%
“…One of the most consistent findings is that heterosexual males manifest more anti-gay hostility on average than do heterosexual females (Brown & Amoroso, 1975;Glassner & Owen, 1976;Gurwitz & Marcus, 1978;Hansen, 1982;Kite, 1984;Laner & Laner, 1979;Millham, et al, 1976;Minnigerode, 1976;Steffensmeier & Steffensmeier, 1974;Storms, 1978;Weis & Dain, 1979). Although this sex dif- ference in attitudes has been observed often, few attempts have been made to explain it (Kite, 1984).…”
mentioning
confidence: 99%
“…Prior to the development of the IHP, Millham, San Miguel, and Kellogg (1976) conducted what appears to be the most methodologically sound investigation of attitudes toward homosexuality. These researchers developed a questionnaire Consisting of 38 items designed to survey a broad range of attitudes and beliefs toward homosexuality.…”
Section: Problems In the Measurement Of Homophobiamentioning
confidence: 99%